2012
DOI: 10.1055/s-0031-1299009
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus Typ 2 und Depressivität: Was ist ursächlich für was?

Abstract: Knowing about this - even causal - co-morbidity is important in care, including a routine diagnostic approach to find out if the other disease is also present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
3
Order By: Relevance
“…Previous research showed that depression is associated with a wide range of physical diseases with the strongest association being reported with cardiovascular diseases ( 18 ), diabetes ( 9 , 10 ), COPD ( 16 ), and chronic musculoskeletal disorders ( 11 , 12 ). However, findings on the direction of the respective associations remain heterogeneous ( 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that depression is associated with a wide range of physical diseases with the strongest association being reported with cardiovascular diseases ( 18 ), diabetes ( 9 , 10 ), COPD ( 16 ), and chronic musculoskeletal disorders ( 11 , 12 ). However, findings on the direction of the respective associations remain heterogeneous ( 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…[7], [8]; for overview: [9], [10]). Comorbid depression is consistently related to diabetes complications (diabetic retinopathy, nephropathy, neuropathy, macrovascular complications, and sexual dysfunction) [11] and also to treatment nonadherence [12].…”
Section: Introductionmentioning
confidence: 99%
“…From previous experience with a similar review [ 16 18 ], we expect studies to be too heterogeneous to allow for a quantitative summary of results. If, however, we find subsets of studies to be homogeneous enough, we will perform meta-analyses for incidence rates by Poisson generalized linear mixed models (GLMM) as recommended by Trikalinos et al [ 19 ].…”
Section: Methods and Designmentioning
confidence: 99%